The Use of Authentic Materials in Teaching Grammar for EFL Students (Teachers Perspective) - Mestari, Sri Agriyanti; Malabar, Fahria (LLT Journal: A Journal on Language and Language Teaching, 2016)
The goal of this paper is to analyze the use of authentic material in teaching grammar for EFL students. Kilickaya (2004) define authentic materials as exposure to real language and use in its own community. Peacock (1997) has another definition of authentic materials which isthe materials that have been produced to fulfill some social purposes in the language community. Authentic materials are assume as the important tools for teachers in class in order to make his/her teaching effective in transmitting the necessary knowledge to all students. This presentation will discuss the effects of using authentic material in teaching grammar from teachers perspective and offer how authentic material can be used in grammar EFL class.